Early-onset movement disorder as diagnostic marker in genetic syndromes: Three cases of FOXG1-related syndrome. (March 2018) - Caporali, Camilla; Signorini, Sabrina; De Giorgis, Valentina; Pichiecchio, Anna; Zuffardi, Orsetta; Orcesi, Simona
Abstract: FOXG1 -related syndrome is a developmental encephalopathy with a high phenotypic variability. A movement disorder presenting at onset is one of the main features, along with microcephaly and severe psychomotor delay without regression. Specific brain MRI findings facilitate the diagnosis. We report three cases of FOXG1 -related syndrome, focusing on clinical onset, brain MRI and evolution over time in order to identify common features despite the three different underlying genotypes (14q12 deletion including the FOXG1 gene, FOXG1 intragenic mutation, 14q12 deletion including PRKD1 and a region regulating FOXG1 expression). In conclusion, we stress the importance of considering genetic syndromes in the differential diagnosis of early-onset movement disorders. Highlights: FOXG1-related syndrome is a quite heterogeneous developmental encephalopathy. Patients with three different genotypes show common clinical features. Early-onset movement disorder can be a diagnostic marker of FOXG1-related syndrome.